In-situ coupled mechanical/electrical investigations on conductive TPU/CB composites: Impact of thermo-mechanically induced structural reorganizations of soft and hard TPU domains on the coupled electro-mechanical properties. (21st September 2022) - Atawa, Bienvenu; Maneval, Léa; Alcouffe, Pierre; Sudre, Guillaume; David, Laurent; Sintes-Zydowicz, Nathalie; Beyou, Emmanuel; Serghei, Anatoli
Abstract: In-situ coupled mechanical/electrical investigations on TPU-based nanocomposite materials filled with carbon black have been carried-out under continuous and cyclic mechanical loading, with simultaneous measurements of stress, strain and electrical conductivity as function of the strain rate and amplitude. The impact of mechanical deformation and thermal treatment on the structure/properties relationship has been investigated by employing SAXS/WAXS, DSC and TEM measurements. Higher conduction properties were through dynamic percolation induced by TPU soft domains crystallization. The TPU hard domains were found to be more sensitive to thermal treatment: annealing at high temperature led to microcrystalline hard domains that strongly influenced the conductivity evolution upon mechanical deformation. Structural and morphological reorganizations induced by mechanical deformation and thermal treatment can be thus efficiently used to adjust the coupled electro-mechanical behavior of TPU-based composite materials. Graphical abstract: Image 1 Highlights: Strain induced crystallization of TPU soft domains enhanced the electrical conductivity. The stress and strain at failure of conductive CB/TPU composite increase with the loading rate. Thermo-mechanical treatment can be used to guide the electrical properties of conductive CB/TPU composite.